Design of DC-DC Boost Converter to Enhance Vertical Axis Wind Turbine Performance - Khairunnisa (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This paper presents a simple control strategy for vertical axis wind turbines using a permanent magnet synchronous generator (PMSG). The performance of the wind turbine is enhanced by a DC-DC Boost converter based on a PID controller. The purpose of this DC-DC boost converter is to maintain the output voltage to have a constant value when the wind speed changes. The dynamic wind speed affected the voltage output of the turbine generator and the input voltage of boost converter as well. The PID controller will make the wind turbines able to operate in wide range of wind speeds. The boost converter output will give feedback to produce the right PWM duty cycle and trigger the mosfet to maintain the voltage when the wind keeps changing. This system has suppressed the value of overshoot and increased the efficiency of wind turbines.